Assessment of documentation of DSM - IV - TR criteria a for diagnosis of schizophrenia in psychiatric unit, tertiary hospital, Malaysia - Maung, Khin Maung; Ohnmar, Htwe; Than, W.; Musa, Ramli; Md Rosli, Najwa Hanim; Al-Ani, Ali Sabri Radeef; Abu Bakar, Ahmad Zafri (Società Editrice Universo (SEU), 2015)
Objective. The purposes of this study were to investigate the documentation of the DSM - IV - TR - Criteria A in diagnoses of schizo - phrenia and to identify the symptoms associated with over diagnosis of schizophrenia Method. This study involved a retrospective review and analysis of data from case notes. Results. Data of 107 newly diagnosed patients with schizophrenia were keyed in a nd analyzed using SPSS v 19. The cases were then evaluated for the use of the DSM - IV - TR - Criteria A. Over diagnosis was noted in 37.39% of the patients. Disorganised behaviour (12.5%), affective flattening (12.5%), hallucination (16%) and non - bizarre delus ion (18.3%) significantly contributed to the over - diagnosis of schizophrenia. Symptoms such as non - bizarre delusion and hallucina - tion were the most commonly used in over - diagnosing schizophrenia and were statistically significant with p ≤ 0.05. Conclusion. There was a significant lack of DSM - IV - TR Criteria A among the data documented to diagnose schizophrenia and non - bizarre delusion and hallucination were the most commonly used in over - diagnosing schizophrenia. This key problem needs to be addres sed. The reliability of a diagnosis is indispensable and achievable with the proper clinical application of DSM - IV - TR Criteria A. The DSM - IV - TR Criteria have been perceived to be useful and reliable and is most widely used throughout the world